THE INFLUENCE OF ENVIRONMENTAL ACCOUNTING DISCLOSURE, ENVIRONMENTAL PERFORMANCE, AND COMPANY SIZE ON FIRM VALUE - Giantoro, Yessica Febriana; Remon Gunanta (Universitas Mercu Buana Yogyakarta, 2025)
This research aims to determine the extent of the influence of environmental accounting disclosure, environmental performance, and company size on company value in LQ-45 Index companies listed on the Indonesia Stock Exchange for the 2019-2023 period. This type of research uses a quantitative approach. The research sample consists of 28 companies listed on the Indonesia Stock Exchange from 2019 to 2023. The data collection technique used is documentation. The data analysis technique applied is multiple linear regression with classical assumption tests, as well as statistical tests including partial t-tests, F-tests, and the coefficient of determination. The results of this study indicate that environmental accounting disclosure negatively affects company value, environmental performance negatively affects company value, and company size positively affects company value.